Social Media Phenomena in Corporate Disclosure Practise (A case study of Nestlé) - Chleitosia Violen Dentya Paradisa Naibaho; Chleitosia Visien Dentya Paradisa Naibaho; Arthik Davianti (Indonesian Management and Accounting Research, 2020)
The use of social media among companies to disclose and disseminate corporate information is rocketing. This study examined to what extent companies use social media platforms, especially Twitter. It identified the disclosure of Multinational Companies (MNCs) in Southeast Asia, particularly Indonesia. The study analyzed Nestlé as it operates in more than half of the countries in Southeast Asia, including Indonesia. The data was based on Nestlé Twitter accounts, both parent and the subsidiary, which is collected from the beginning of the year to December 31st, 2019. This study utilized a descriptive qualitative method using content analysis in the form of a case study to analyze the information shared and disclosed by this consumer goods company. The results showed that Nestlé uses Twitter for disclosing information that covers environmental, branding, health, gender, education, and others. It is found that Nestlé parent company disclosed more data than its subsidiary in Indonesia, and content shared by Nestlé Indonesia is quite different because of cultural differences. Indonesia’s subsidiary followed the pattern of information disseminated by their parent companies on its Twitter account. Overall, the results indicated that Twitter is rarely used in Southeast Asia for many disclosure purposes, either financial or non-financial information.